EFFECT OF CHEWING MARSHMALLOW CONTAINING BETEL CHEW IN REDUCING STREPTOCOCCUS MUTANS AND PLAQUE INDEX ON CHILDREN - RINDIT PAMBAYUN; ADE PUTRI; MEIDY TRI YUDA; SITI RUSDIANA PUSPA DEWI; TRI WARDANI WIDOWATI; BUDI SANTOSO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Marshmallow is a soft candy loved by all levels of society, especially children. Sucrose contained in marshmallow increases the growth of Streptococcus mutans and plaque. Betel chew as Indonesian traditional plants add in marshmallow was believed to decrease S. mutans and plaque. The aim of this study was to evaluate the effect of chewing marshmallow containing betel chew in reducing S. mutans and plaque index in children. Methods: This research was a quasi-experimental with pre-test and post-test control group design. It was conducted in the Laboratory of Agricultural Chemistry, Laboratory of Agricultural Technology Department, and Islamic School of Al-Amalul Khair. Thirty students were divided into two groups. Group A was chewing marshmallow without betel chew and Group B was chewing marshmallow containing betel chew. Results: The results showed that chewing marshmallow without betel chew increased the growth of S. mutans and plaque index significantly. Chewing marshmallow without betel chew inhibited the growth of S. mutans and dental plaque formation. Conclusion: Chewing marshmallow containing betel chew reduces S. mutans and plaque index on children.